Political Cycles’ Influence on Inflation and Unemployment - Rakić, Biljana; Stanojević, Jelena; Rađenović, Tamara (Industrija, 2015)
The aim of the research is to show the relationship between political parties and voters and its impact on economic situation in the pre and post-election period. The paper points out the interaction between economics and politics, the behaviour of an individual in the economic and political market and analyses the economic models that study the response of voters to different political programmes. An overview of all political elections in the Republic of Serbia since 2000 and the inflation and unemployment rates during the same period is also provided in order to confirm the hypothesis that inflation and unemployment in the pre-election period are in the function of political interests, while in the post-election period they return to their initial level.